2012
DOI: 10.1128/jcm.05900-11
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Streptococcus dysgalactiae, Its Subspecies, and Its Clinical and Phylogenetic Relationship to Streptococcus pyogenes

Abstract: The taxonomic status and structure of Streptococcus dysgalactiae have been the object of much confusion. Bacteria belonging to this species are usually referred to as Lancefield group C or group G streptococci in clinical settings in spite of the fact that these terms lack precision and prevent recognition of the exact clinical relevance of these bacteria. The purpose of this study was to develop an improved basis for delineation and identification of the individual species of the pyogenic group of streptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
85
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 56 publications
(65 reference statements)
6
85
1
1
Order By: Relevance
“…Frequent homologous recombination within and between Streptococcus species renders identification based on sequences of single loci problematic (5,14,15,17,18,23). With this background, it is remarkable that the cytosine at position 203 in the 16S rRNA gene of S. pneumoniae appears to be fully conserved in the population of S. pneumoniae while strains of all other mitis group streptococci have an adenosine at this position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequent homologous recombination within and between Streptococcus species renders identification based on sequences of single loci problematic (5,14,15,17,18,23). With this background, it is remarkable that the cytosine at position 203 in the 16S rRNA gene of S. pneumoniae appears to be fully conserved in the population of S. pneumoniae while strains of all other mitis group streptococci have an adenosine at this position.…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus sequence analysis (MLSA) eliminates the potential problems resulting from homologous recombination and has been applied with success in the identification of several bacterial species that are difficult to differentiate by simpler methods (5,13,17,18,23,29,25,33). Schemes based on four to seven gene loci have proven valuable in differentiation of Streptococcus species (5,17,18). Specifically, an MLSA-based procedure for identification of S. pneu-moniae was reported by Hanage et al (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the S. mitis group, including S. pneumoniae, are closely related, and even the discriminatory power of the 16S rRNA gene is too low for reliable differentiation (2). However, due to clinical reasons, the differentiation of S. pneumoniae is of critical importance, and additional tests are required in case of a MALDI-TOF MS S. pneumoniae identification, (24). Nevertheless, differentiation of these two species is required in the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have characterized strains only from invasive infections. However, three studies compared invasive and noninvasive infections, and these studies found a correlation between emm type and invasive disease potential (3,27,31). In these studies, stG6, stG10, stG480, stG485, stG2078, and stG6792 were described as invasive emm types.…”
mentioning
confidence: 99%